Active learning: review among Faculty of Business and Management students / Junaida Ismail ... [et al.] - Ismail, Junaida; Harun, Etty Harniza; Musa, Aishah; Bidin, Samsiah; Abd Jalil, Muna; Ali, Meriam (Universiti Teknologi MARA, 2021)
This paper describes one of the criteria for student's success in learning which is student engagement. Active learning is one of the platforms to enhance student engagement. However, active learning is rarely used as a learning tools at the tertiary level. According to the National Survey of student Engagement (NSSE) and the Australian survey of students Engagement (AUSSE), active learning involves "students' efforts to actively construct their knowledge". As cited in Brame (2016), active learning is desired as "activities that students do to construct knowledge and understanding". Thus, to venture into the issues of active learning this study is constructed to determine the students' perceptions of active learning. The students were given a set of survey to rate their perceptions towards active learning approach that was being applied by their respective lecturer. Their ratings were gathered and analysed using SPSS Software. In total there were 166 respondents from Faculty Business Management of UiTM Kedah. Majority of the respondents were female with 118 students. The findings revealed that majority of respondents preferred active learning as it helped them to remember things better, enjoyed the lesson and improved their social skills. It is hoped that this study will provide good understandings to lecturers in terms of promoting their creativity in teaching especially in applying active learning approach.